THE PHENOMENON OF TURN OF THE MONTH EFFECT ON INDONESIAN, JAPANESE AND AMERICAN STOCK EXCHANGES BEFORE, DURING AND AFTER THE COVID-19 PANDEMIC - Syifa Maudina; Siti Komariah (Jurnal Ekonomi, 2023)
The quality of the capital market can be determined by the concept of an efficient capital market. However, there are many deviations from the efficient capital market, one form of which is the Turn Of The Month Effect market anomaly. This phenomenon illustrates a higher rate of return at the beginning of the month than at the end of the month. This study aims to understand how the Turn Of The Month Effect event affects the Indonesian (LQ45), Japanese (Nikkei), and American (Dow Jones Industrial Average) stock indices during the Covid-19 pandemic period from 2019-2021. As well as to find out the difference in the rate of stock return on the IDX (LQ45) between the beginning of the month and the end of the month and the middle of the month, also to see the difference between stock returns in Indonesia, Japan, and America during the research period because there was an extreme stock value due to the impact of the Covid-19 pandemic which had an effect on stock values ​​and the global economy. This study uses daily index data from January 2019 to December 2021 for each country. Comparative method and event study are the methods used in this research.Normality test, paired sample t-test and different test are the analytical techniques used in this study.The results of the study prove that there is no Turn Of The Month Effect in LQ45, Nikkei, and DJIA during the study period.